Effects of RAMEB and/or mechanical mixing on the bioavailability and biodegradation of PCBs in soil/slurry. (July 2016) - Hu, Jinxing; Wang, Yalin; Su, Xiaomei; Yu, Chunna; Qin, Zhihui; Wang, Hui; Hashmi, Muhammad Z.; Shi, Jiyan; Shen, Chaofeng
Abstract: Microbial remediation is preferred as a clean and cost-effective method for restoring environments polluted by organics. But the biodegradation rates of hydrophobic organic contaminants (HOCs) are usually extremely restricted by their low bioavailability, especially in soil. Here, a physical method (mechanical mixing) and a chemical method (randomly methylated- β -cyclodextrins, RAMEB) were adopted to improve the bioavailability and biodegradation of polychlorinated biphenyls (PCBs) of an aged soil. The bioavailability of tri-CBs was increased by adding RAMEB in soil/slurry or assisting mechanical mixing in slurry, but these methods had no effects on the bioavailability of tetra-CBs and high chlorinated PCBs (Cl > 4). The degradation rate of tri-CBs could be obviously enhanced by adding RAMEB in soil or assisting mechanical mixing in slurry. The highest removal amount of tri-CBs reached 43.8% in 100 d with a first-order decay kinetics constant of 0.0059 d −1 . But the removal of tetra-CBs and high chlorinated PCBs (Cl > 4) were not significant in all mesocosms, possibly due to the lack or weakness of the native degrading microflora. Based on the analysis of the richness and diversity of bacterial communities, the characteristics of the heatmap and the variation of bphC copy numbers in the soil/slurry mesocosms, it could be inferred that there was no obvious corresponding relationship between the variation of the bacterial communities and the physical/chemical measures. Highlights: Bioavailability of tri-CBs were increased by RAMEB or mechanical mixing. Non-bioavailable tri-CBs could transform into bioavailable tri-CBs. Degradation of tri-CBs could be enhanced by RAMEB or mechanical mixing. Total amount and bioavailability of PCBs (Cl ≥ 4) were kept stable in all mesocosms. Soil/slurry bacterial richness and diversity presented an overall downward trend.